KEDUDUKAN DAN KEWENANGAN BAWASLU DALAM STRUKTUR LEMBAGA NEGARA INDONESIA (Lex Jurnalica, 2018)
AbstractThe presence of additional independent state institutions is becoming increasingly important in order to keep the process of democratization being developed by a state that has just detached itself from the authoritarian system. It is in this context that Bawaslu is positioned as a driver of the democratization process through election activities. In this study, the authors formulate two (2) problems are (1) How Bawaslu position in the structure of state institutions of Indonesia? (2) How Bawaslu's tasks, functions and authorities are. The research method used is normative method. From the results of research that the authors do. Bawaslu position in Indonesian citizenship structure is as an auxiliary state organs institution. The presence of Bawaslu because the government no longer has the credibility to hold a fair and democratic elections. With Law No. 7 of 2017 on the new General Election has strengthened both the composition, duties, and authority of Bawaslu. First, Article 89 shows the Regency / Municipal Panwaslu has been changed to Bawaslu Kabupaten / Kota. Second, Article 93 indicates that Bawaslu is also responsible for overseeing the neutrality of the State Civil Apparatus (ASN), TNI and Polri. Third, Section 95 shows Bawaslu as an executing agency or breaks off administrative violations, money politics violations, and dispute resolution. The results of this study the authors provide advice to be given a good debriefing to members of Bawaslu both Central, Provincial and District / City to be able to properly perform new duties and authorities. Keywords: bawaslu, position, authority AbstrakKehadiran lembaga negara tambahan independen menjadi semakin penting dalam rangka menjaga proses demokratisasi yang tengah dikembangkan oleh negara yang baru saja melepaskan diri dari sistem otoritarian. Dalam konteks inilah Bawaslu diposisikan sebagai penggerak proses demokratisasi melalui kegiatan pemilu.Dalam penelitian ini, penulis merumuskan dua (2) permasalahan yaitu (1) Bagaimana kedudukan Bawaslu dalam struktur lembaga negara Indonesia? (2) Bagaimana tugas, fungsi, dan kewenangan Bawaslu. Metode penelitian yang digunakan adalah metode normatif. Dari hasil pembahasan yang penulis lakukan. Kedudukan Bawaslu dalam struktur kelembaganegaraan Indonesia adalah sebagai lembaga negara tambahan negara independen (auxiliary state organs).Kehadiran Bawaslu dikarenakan pemerintah tidak lagi memiliki kredibilitas untuk menyelenggarakan pemilu yang adil dan demokratis. Dengan UU Nomor 7 Tahun 2017 tentang Pemilu yang baru telah memperkuat baik susunan, tugas, serta kewenangan Bawaslu. Pertama, Pasal 89 menunjukkan Panwaslu Kabupaten/Kota telah berubah menjadi Bawaslu Kabupaten/Kota. Kedua, Pasal 93 menunjukkan Bawaslu juga bertugas mengawasi netralitas Aparatur Sipil Negara (ASN), TNI dan Polri. Ketiga, Pasal 95 menunjukkan Bawaslu sebagai lembaga eksekutor atau memutus pelanggaran administrasi, pelanggaran politik uang, dan penyelesaian sengketa.Hasil penelitian ini penulis memberikan saran agar diberikan pembekalan yang mumpumi kepada anggota Bawaslu baik Pusat, Provinsi maupun Kabupaten/Kota agar bisa dengan baik menjalankan tugas dan wewenang yang baru. Kata kunci: bawaslu, kedudukan, kewenanangan